The Rhetoric of Travel: Persuasion Tools in the Lithuanian Travel Literature - Gibavičienė, Gabrielė (Respectus Philologicus, 2018)
Rhetoric which in the context of this research is seen not only as a structure of text but also as a structure of thought is presented in the article as a new universal way of researching Lithuanian travel literature discourse. Three popular Lithuanian travel books are chosen for this research – Kelionė į Jeruzalę (Journey to Jerusalem, 1601) by Mikalojus Kristupas Radvila Našlaitėlis, Svečiuose pas 40 tautų (At the Company of 40 Nations, 1935–1936) by Matas Šalčius, and Sapnuoju, kad einu (Dreaming the Path, 2014) by Jokūbas Vilius Tūras. The article presents the research of three persuasion tools ethos, logos and pathos in Lithuanian travel literature and how they are involved in successful communication process. The article reveals exactly how trusting the author and presenting actual traveller’s experience is connected with stimulating audience’s emotions and what part in this process is taken by the journey itself. The article also analyses how the enthymeme is involved in achieving persuasion and how it captures traveller’s views, communication guidelines and common features of different travel texts.
Keywords: Lithuanian Travel Literature; Ethos; Logos; Pathos; Persuasion